Acute and chronic pulmonary responses to intratracheally instilled Benzo (A) pyrene in rats - Mazlan, Mazlina (2010)
Air pollution has been reported to exert serious health effects to all living things in both short and long term exposures. These allegations have been proven by mounting epidemiological data and studies which consistently showed clear evidences. However, the precise mechanisms behind the association between airborne particulates and the evidences have yet to be fully comprehended. Benzo(a)pyrene (BaP) is a main constituent of haze and notably known to be the cause of mutagenicity and carcinogenicity in experimental animals. Despite the notorious reputation of BaP, no conclusive study has been conducted to assess the effects of this compound at such a low dose as the one that Malaysians encountered during the haze episode in 1997. Thus, this study was designed to assess the oxidative stress in rats intratracheally exposed to BaP, and also to correlate these findings with the morphology of the lungs. This study involved a total of 70 rats, divided into groups of 5 rats each and randomly assigned to different treatment groups. A total of 50 rats and 10 rats were assigned to the acute and chronic responses, respectively. The remaining 10 rats were used as controls. The rats that were assigned in acute study were instilled intratracheally with a single dose of 13.8 ng which is equivalent to 7 ul of BaP. In contrast, the rats destined to receive BaP in the chronic response were given 2 doses of equal amountd which have been divided equally (3.5 ul) with the second dose administered at 1 week post instillation (p.i). All the rats were alternately subjected to blood sampling via intra cardiac puncture at hours (hr) 0, 1, 8, 16, 24, 32, 72 (acute) and weeks (wk) 1, 3, 6, 9, 12 (chronic) p.i. However, 5 rats in the treated group were euthanized at 1, 8, 16, 32 and 72 hr p.i. for the acute response study. Rats in the chronic response and the control groups were only sacrificed at 12 wk p.i. At necropsy, lung samples were collected for morphological studies. The antioxidant and lipid peroxidation assays were conducted on blood, lungs and liver samples. Acute response revealed a marked inflammatory response characterized by predominantly alveolar macrophages and mild neutrophils infiltration at 8 hr and 16 hr p.i. in the BaP group. These lesions corresponded to the high malondialdehyde (MDA) and superoxide dismutase (SOD) with low glutathione peroxidase (GSH-Px) and glutathione S transferase (GST) concentrations in the blood, lungs and liver. The chronic response revealed that the treated group demonstrated mild inflammatory reactions with persistent hyperplasia, metaplasia and dysplasia of the pneumocytes with presence of granuloma at 12 week p.i, Diffused emphysema of the lungs was the obvious lesion seen in the chronic study. The MDA and SOD activities in the peripheral blood, lung and liver of treated rats were significantly (P<O.05)high at 12 weeks p.i. On the contrary, the level of GSH-Px of treated rats in all of the samples (blood, lungs and liver) and was significantly (P<O.05)lower at 12 wk p.i, Likewise, the GST level in the lung and liver of treated rats were significantly (P<O.05) lower than the normal rats at 12wk p.i. It was concluded that even at minute levels, BaP is able to exert deleterious effects on tissue morphology via oxidative stress as evident from the disruption in the lipid peroxidation (MDA level) and antioxidant status (SOD,GSH-Px and GSTlevels) in blood, lungs and liver.